Ghanaian women in sports: Barriers and strategies for improving participation in sports leadership positions in Ghana - Nkrumah Adasa, Abena; Apaak, Daniel; Addae Kyekyehene, Stephen; Domokyile Nayasama, Jude (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The study explored the barriers that hinder women’s participation in sports leadership in Ghana and the effective strategies to overcome the obstacles. Interpretivist research paradigm was adopted. Sample frame was made of women leaders in Ghanaian sports organizations. Data was collected using interview guides, and analyzed with the Interpretative Phenomenological Analysis (IPA). The study revealed that institutional barriers and individual mindsets of women in sports were among the most significant factors limiting women’s leadership involvement. Promoting women’s education and fostering a broader shift in organizational culture can lead to increased female representation in professional sports organizations. In conclusion, further quantitative and qualitative research is needed to understand why women’s participation in sports leadership is not adequately reflected in current legislation or outdated sports policies.